Um estudo com professores supervisores do Pibid sobre suas compreensões/ações acerca da avaliação do ensino e aprendizagem - Oliveira, Luciani de (2017)
From the insertion of the Institutional Scholarship Program for Initiation to Teaching in the universities, it was possible to extend to undergraduate students the approach to the school environment. This makes it possible to go beyond the opportunities provided by supervised internships and teaching practices, since the presence of the teachers of the schools in the universities facilitates discussions experienced in the school context. One of the themes that emerges from these discussions, carried out by the different participants, is anchored in the evaluation of teaching and learning. Faced with this, much has been questioned about the ways of assessing and the conflicts related to them that, at times, can affect the teaching work. Thus, this research sought to highlight the contributions of the Institutional Program of Initiation Scholarships to teaching in the training of three supervisors and how they understand and practice the evaluation of teaching and learning. As a data collection tool, we used a questionnaire to verify the teachers' conceptions about the evaluation and contribution of the Institutional Program of Initiation Scholarships to Teaching in their teaching work. We then followed up with a content with the participants to check if there is a dichotomy between theory and practice. Subsequent to the analysis of these two instruments, a semi-structured interview was proposed in order to inquire the teachers from the previous analysis of the questionnaire and the follow-up form. In order to relate these phenomena through the triangulation of the data collection instruments with the research problem, we chose to use Discursive Textual Analysis. The present research evidenced how the evaluation is inserted in the teaching work of the supervising teachers, as well as how the Institutional Program of Initiation to Teaching / Biology has contributed in its Continuing Education, in which from the analysis it was possible to show that: are closer to the aspects of a traditional teacher, because, although they perform diverse evaluative activities, their classes and their instruments are little different from the traditional evaluation; and another that approaches an intellectual teacher, because his classes allow the critical reflection of his students. With this, we consider that it is important to discuss the evaluation of teaching and learning within the undergraduate courses, as well as the subprojects of the Institutional Scholarship Program.